2023
DOI: 10.3390/ma16237363
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Geopolymer Materials: Properties, Environmental Impacts, and Applications

Sami Sbahieh,
Gordon McKay,
Sami G. Al-Ghamdi

Abstract: The advancement of eco-friendly technology in the construction sector has been improving rapidly in the last few years. As a result, multiple building materials were developed, enhanced, and proposed as replacements for some traditional materials. One notable example presents geopolymer as a substitute for ordinary Portland concrete (OPC). The manufacturing process of (OPC) generates CO2 emissions and a high energy demand, both of which contribute to ozone depletion and global warming. The implementation of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 177 publications
1
4
0
Order By: Relevance
“…The CV ranges from 0.82% to 1.85% for the primary impact "Human toxicity", suggesting that there is relatively low uncertainty in the calculated values for these impacts. The results of this study are comparable with other studies, as Miyan et al [29] found that recycled waste concrete consistently reduced carbon emissions, cumulative energy demand, and costs, where alkaline solutions are a hotspot accounting for a significant portion of the impacts [29,35,50]. Therefore, Munir et al [51] obtained industrial-based geopolymer concrete with an improved environmental performance using lower quantities of sodium silicate.…”
Section: Monte-carlo Simulationsupporting
confidence: 87%
See 1 more Smart Citation
“…The CV ranges from 0.82% to 1.85% for the primary impact "Human toxicity", suggesting that there is relatively low uncertainty in the calculated values for these impacts. The results of this study are comparable with other studies, as Miyan et al [29] found that recycled waste concrete consistently reduced carbon emissions, cumulative energy demand, and costs, where alkaline solutions are a hotspot accounting for a significant portion of the impacts [29,35,50]. Therefore, Munir et al [51] obtained industrial-based geopolymer concrete with an improved environmental performance using lower quantities of sodium silicate.…”
Section: Monte-carlo Simulationsupporting
confidence: 87%
“…However, this shift may lead to a significant increase in other environmental impacts due to the use of alkaline activators or grinding. Sbahieh et al [50] confirmed that the geopolymer concrete has lower carbon emissions compared to OPC concrete during manufacturing, yet it presents minor adverse environmental effects, including abiotic depletion, human toxicity, freshwater ecotoxicity, terrestrial ecotoxicity, and acidification.…”
Section: Environmental Impact Analysis Of Geopolymer Mortar MIXmentioning
confidence: 99%
“…The harmless treatment of electrolytic manganese slag mainly includes water washing [ 4 ], acid leaching [ 5 ], electrokinetic restoration [ 6 ], solidification/stabilization (solidification/stabilization, S/S) technology [ 7 ], and other routes. The first three methods have high processing costs and complex technical routes, with scholars now favoring efficient, energy-saving, easy-to-operate S/S technology; compared with other S/S technologies, geopolymers have the advantages of fast setting and early strengthening, good durability, inexpensive costs, and low carbon emissions, which have attracted the attention of researchers [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its superior strength and durability, GPC offers a myriad of advantages, establishing itself as a compelling choice for contemporary construction practices [4]. Notably, GPC exhibits exceptional early-age strength and benefits from ambient curing conditions, contributing to accelerated construction timelines [5]. The intricacies of GPC's durability and strength hinge on various factors, including the selection of binders, the alkali-activating solution employed, and the nuances of the curing process [6].…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers have emerged as a focal point in contemporary research and development, holding substantial promise as ecologically beneficial and sustainable alternatives to traditional cement-based materials [5]. The impetus behind geopolymer research lies in its potential to significantly alleviate the environmental impact associated with conventional Portland cement production [20].…”
Section: Introductionmentioning
confidence: 99%